Spotlight on dupilumab in the treatment of atopic dermatitis: design, development, and potential place in therapy - D'Erme AM; Romanelli M; Chiricozzi A (Dove Medical Press, 2017)
Angelo Massimiliano D’Erme,1,2 Marco Romanelli,2 Andrea Chiricozzi2 1Dermatology Unit, Livorno Hospital, Livorno, 2Dermatology Unit, Department of Clinical and Experimental Medicine, University of Pisa, Pisa, Italy Abstract: Atopic dermatitis (AD) is among the most common inflammatory skin diseases in children and adults in industrialized countries. Up to one-third of adults (probably a smaller proportion in childhood) suffer from moderate-to-severe AD, whose recommended treatment is usually based on systemic therapies. The currently available therapeutics are limited, and AD management becomes challenging in most cases. Over the last few years, new advances in the understanding of AD pathogenic mechanisms and inflammatory pathways have led to the identification of specific therapeutic targets and new molecules have been tested. Dupilumab is a fully human monoclonal antibody directed against the IL-4 receptor α subunit that is able to block the signaling of both IL-4 and IL-13 and achieve rapid and significant improvements in adults with moderate-to-severe AD. Dupilumab is ready to inaugurate a long and promising biological target treatment option for Th2 cell-mediated atopic immune response that characterizes AD. Keywords: dupilumab, atopic dermatitis, eczema, IL-4, IL-13, biologics